SSM: Secure-Split-Merge data distribution in cloud infrastructure - Khan, Burhan ul Islam; Olanrewaju, Rashidah Funke; Baba, Asifa Mehraj; Ahmad Lone, Sajad; Zulkurnain, Nurul Fariza (IEEE, 2015)
With the advancement of cloud storage services the vulnerabilities associated with cloud-related data has increased. It affects the cloud distributed data servers that are not only used for data storage, but also used for managing a huge amount of data with distributed file structures in collaborative sharing. The data sharing processes of cloud computing infrastructure are susceptible to various kinds of attacks where many traditional cryptographic techniques fail to provide a proper and efficient authentication mechanism. In this paper, a novel approach namely Secure-Split-Merge (SSM) is introduced for the security of data. The proposed SSM scheme uses a unique mechanism of performing splitting of data using AES 128 bit encryption key. The chunks of encrypted splits are being maintained on various rack servers of different types of cloud zones. The comparative analysis shows that the proposed system gives effective outcomes as compared to various existing and traditional security standards.